Use of network theory and reliability indexes for the validation of synthetic water distribution systems case studies. (December 2017) - Paez, D.; Filion, Y.
Highlights: A method to generate synthetic WDSs models was validated using 45 synthetic and 15 real life systems. The connectivity comparison showed the need to increase the meshedness coefficient of the synthetic systems. After the improvement the 45 synthetic systems performed acceptably when compared with the 15 real-world ones. Abstract: The examination of the relationship between energy use, reliability and network characteristics in water distribution systems (WDS) requires a set of sufficient case studies to give statistical significance to the conclusions. Considering the difficulty of finding real-world systems that can be used in this kind of research, synthetic (virtual) distribution systems are the next available alternative to use as case studies. This paper describes the use of a new method for the generation of synthetic distribution systems and its subsequent comparison against real-world systems to validate the suitability of the synthetic set to drive the conclusions of future research. The algorithm for the generation of synthetic WDSs is based on the work, methods and software presented by Mair et al. (2014). For the validation procedure, five metrics or indexes that account for the network's connectivity (link density, average node degree, meshedness coefficient) and the system's reliability (Resilience Index, Network Resilience) are evaluated; the ranges in each of the metrics are then compared. The generation of synthetic WDS required an enhancement of the connectivity of the networks and a pipe sizing that accounted for practical system design. An acceptable degree of similarity between the synthetic and the real-life sets of WDSs was achieved, although some modifications to the networks may be required in the future.